Literary Braille Instruction: A Review of University Personnel Preparation Programs. (September 2022) - Farrand, Kathleen M.; Koehler, Karen; Vasquez, Ananí
Introduction: Braille literacy for students who are visually impaired (i.e., those who are blind or have low vision) can be a critical component for school and postsecondary transition success. This survey study was a modified replication of previous studies that examined the instruction of literary braille in university preparation programs for professionals who work with students with visual impairments.Methods: Nineteen university instructors of literary braille responded to a survey about instructional formats, books, and tools, as well as assessment issues, such as test formats, scoring, and requirements for demonstrating proficiency.Results: Survey responses indicated that some instructional strategies at the university level have remained the same over the last 20 years, but there are also some changes. Most notably, updated books and resources are being used and instructors represent the same demographic group, Caucasian females over 45 years old. But, the level of experience has substantially dropped and there has been a shift to increased online learning. All programs indicated focusing instruction on Unified English Braille (UEB) code.Discussion: Prior concerns about the challenges of teaching UEB have been somewhat satisfied. Proficiency exams are now required by programs, which could contribute to better prepare teachers for students with visual impairments.Implications for Practitioners: The shift to online learning affects practice. The use of braille simulation software might alter the way practitioners think about erasures. In preparing for distance learning, instructors must consider how to make courses accessible, rigorous, and of high quality. Although university braille proficiency exams should continue to be used to evaluate the skills of future professionals, educators might advocate for tests at the state or province level prior to licensure and common standards for minimal competency.